EFFECT OF DIFFERENT SURFACE ROUGHNESS ON GLUE STRENGTH OF POLYVINYL CHLORIDE SHEET - MA XiaoSong; XING YouDong (Jixie qiangdu)
In order to verify the strength of polyvinyl chloride（pvc） plastic sheet lap joint with different surface roughness, the pvc plate was polished with different mesh sandpaper（polished length was 30 mm）. The surface roughness was measured with a surface roughness instrument and the surface was examined with a high power microscope. The results show that different types of sandpaper abrasive sheet will produce different surface roughness. 60 mesh to 400 mesh sandpaper polished sheet surface roughness decreased gradually, the performance of the Ra value from 10.840 μm reduced to 1.503 μm. Tensile strength test was carried out by bonding the sheet with different surface roughness to the silicone rubber, and the overlapped plate material with different surface roughness produced different overlapping strength. The maximum tensile force that can be sustained by the lap joint with 60 mesh to 100 mesh sandpaper increased from 1.858 kN to 2.063 kN, and the overlap strength increased gradually. The maximum tensile force that can be sustained by the lap joint with 100-400 mesh sandpaper was reduced from 1.563 kN to 1.567 kN, and the overlap strength is reduced gradually. The control group has no surface treatment of the plate lap joints, can withstand the maximum tensile force of 1.380 kN, is the lowest overlap strength. So for the pvc plastic sheet and silicone rubber lap joints, with 100 mesh sandpaper grinding,the lap performance is the best.